Molecular analysis of eight splicing variants in the hydroxymethylbilane synthase gene - Ren, Yi; Wang, Jiajia; Li, Shuang; Lei, Jiajia; Liu, Yunfeng; Wang, Yan; Gao, Fei; Wang, Jianhong; Yin, Jianhong; Yang, Jing (Frontiers in Genetics, 2023)
Mutations affecting RNA splicing are an important cause of an increasing number of rare diseases, but are often overlooked in in the process of gene detection and variant interpretation. Hydroxymethylbilane synthase(HMBS) gene mutation cause Acute intermittent porphyria(AIP) , a rare autosomal dominant disease of heme metabolism that shows variable clinical expressivity. Molecular genetic testing is the most sensitive and specific method to confirm AIP, especially for individuals with latent AIP, and it helps high-risk family members prevent potentially attacks. So far, more than 500 HMBS gene variants have been reported in the Human Gene Mutation Database (HGMD), of which about 20% affect pre-RNA splicing. Previously, seven variants (c. 33+5G>A, c.88-16_88-4del, c.88-2A>G, c.161-1G>C, c.652-1G>A c.772-2A>G and c.772-1G>C, )have been reported to be linked with AIP, but specific molecular characteristics have not been described so far. Herein, we identified a novel heterozygous variant in HMBS gene (c.160 +5 G>C) from a Chinese family with AIP. With the use of a valid and novel in vitro minigene assay, we demonstrated that all the eight variants caused splicing defects in the pre-mRNA of HMBS gene, which provides PS3 evidence according American College of Medical Genetics and Genomics(ACMG) guidelines. Additionally, we performed RNA extraction from the blood of individuals carrying this novel variant (c.160 +5 G>C) , and the RT-PCR results were consistent with the minigne assay results, which further demonstrated the reliability of our in-vitro experiments. This study provides a molecular basis for future exploration of the pathogenesis and gene therapy of AIP.